2017
DOI: 10.1902/jop.2016.160438
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Synthetic Peptide LyeTxI and LyeTxI/β‐Cyclodextrin Association Compound Against Planktonic and Multispecies Biofilms of Periodontal Pathogens

Abstract: LyeTxI and LyeTxI/βCD are active against periodontopathic bacteria, showing rapid bactericidal effect and may be used to prevent biofilm development. In the future, AMPs could be therapeutic tools for treatment of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Moreover, this peptide inhibits periodontal pathogens and epithelial cells proliferation ( Consuegra et al, 2013 ). Recently, our group showed that LyeTxI and its formulation in beta-cyclodextrin, besides being active against periodontopathic bacteria, can also be used to prevent biofilm development ( Cruz Olivo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this peptide inhibits periodontal pathogens and epithelial cells proliferation ( Consuegra et al, 2013 ). Recently, our group showed that LyeTxI and its formulation in beta-cyclodextrin, besides being active against periodontopathic bacteria, can also be used to prevent biofilm development ( Cruz Olivo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we synthetized a cationic peptide, LyeTx I-b, based on a peptide isolated from the venom of Lycosa erythrognatha spider. This peptide showed strong antimicrobial activity against Gram-positive and negative bacteria including planktonic and multispecies biofilms of periodontal pathogens under various conditions with slight hemolytic activity (Santos et al 2010;Reis et al 2018;Cruz Olivo et al 2017). LyeTxI-b is a synthetic 24-mer peptide (IWL-TALKFLGKNLGKLAKQQLAKL-NH2), which comprises a His16 deletion and N-terminal acetylation, resulting in an improved effect against resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…8 Beyond that, LyeTx I alone and 1:1 LyeTx I/β-cyclodextrin inclusion compound are effective against periodontal pathogens with rapid bactericidal effect and capable to reduce metabolic activity of planktonic and 2-day multispecies biofilm cells at concentrations <250 µg·mL −1 . 9,10 Further studies suggested that LyeTx I amino-terminal side is indispensable to the secondary structure conformation of the peptide, influencing its interaction with bacteria, once either the modification of LyeTx I carboxyl-terminal side (LyeTx I-K-HYNIC) or the suppression of a histidine residue in the same portion (LyeTx I-b) does not compromise its antimicrobial activity. 11,12 Recently, LyeTx I-b was formulated with carboxymethylcellulose and showed activity against a strain of Staphylococcus aureus resistant to penicillin, erythromycin, and ampicillin, acting in planktonic condition and reducing biofilm viability in 90%.…”
Section: Introductionmentioning
confidence: 99%